A study of the dreams and unconscious fantasies of the narrator of Ana Clavel’s novel “Las Violetas son las flores del deseo" (Ogigia. Revista Electrónica de Estudios Hispánicos, 2016)
In this work we analyze the dreams and dreamlike fantasies as main elements of Ana Clavel’s novel Las Violetas son las flores del deseo. The perverted nature of the main character allows us to make an interpretation of his dreams from a psychoanalytic perspective. The Mexican writer draws upon psychoanalytic notions to speak about the subjective emotions of this character, illustrating him as having a complex psychological characterization.
Keywords: literature; psychoanalysis; symbology; dream; characterization